Practical Application of Miyazaki Jitokko Chickens Selected for a Superior Allele at a Single Nucleotide Polymorphism Site in the Cholecystokinin Type A Receptor Gene - Shojiroh Horinouchi; Hiromi Nakayama; Tadahiro Ando; Hideaki Takahashi (The Journal of Poultry Science, 2021)
This study aimed to examine 1) whether selection for a superior allele at a single nucleotide polymorphism site (SNP; AB604331, g.420 C>A) of the chicken cholecystokinin type A receptor (CCKAR) gene in Miyazaki Jitokko chickens is detectable in commercial poultry farms, and 2) whether the reproductive traits of the Kyushu Rhode hens, as a maternal stock line of the Miyazaki Jitokko chickens, are affected by SNP selection. Conventional and A-allele fixed (improved) Miyazaki Jitokko chicks were hatched on the same day and raised in a battery cage until 7 days of age. The chicks were then deposited at two commercial poultry farms and reared until slaughter at 126 and 163 days for cockerels and pullets, respectively. Body weight on the day of hatching (day 0), at 5 days of age, and at slaughter were measured. The differences in the body weights of the farm and test groups at slaughter were analyzed using the generalized linear model. A-allele fixation increased the body weight at slaughter by approximately +123.5 g and +131.9 g in cockerels and pullets, respectively. No significant differences between the conventional and improved hens were detected in terms of egg-laying rate, fertilization rate, and hatchability in the Kyushu Rhode hens. The data suggest that fattening chicks can be supplied as usual, even if Kyushu Rhode hens are switched from the conventional to improved type. In conclusion, genetic improvements using the CCKAR SNP site as a marker were effectively established in terms of the growth of the Miyazaki Jitokko chickens in commercial farms and the reproductive traits of the Kyushu Rhode hens.